Students’ Voices about Education Quality of a Bachelor Program in Pandemic Times - Ávila Martin, Karen Dayanna; Rodríguez Granados, Ingrid Johanna (Universidad Pedagógica y Tecnológica de Colombia, 2022)
During 2020, a series of quarantines that interrupted face-to-face education were experienced. This study aims at examining aspects that impacted the quality of education of a group of five preservice teachers, who moved from face-to-face to virtual learning. We followed a qualitative narrative research design and the participants’ narratives and logs were compiled as data collection instruments. We concluded that methodology, strategies and levels of well-being and health impacted the participants’ educational quality during the onset of the pandemic, and opportunities for the bachelor program to foster better learning-teaching processes were identified. Key words: education, pandemics, quality, story, virtual learning.